2023
DOI: 10.3390/ijerph20186777
|View full text |Cite
|
Sign up to set email alerts
|

Satisfied with Life? The Protective Function of Life Satisfaction in the Relationship between Perceived Stress and Negative Mental Health Outcomes

Anita Padmanabhanunni,
Tyrone B. Pretorius,
Serena Ann Isaacs

Abstract: Life satisfaction is a key index of well-being, yet few studies have examined its role as a protective factor in the context of the COVID-19 pandemic. The current study expands the research in this area through an examination of the role of life satisfaction in the relationship between perceived stress and negative indices of mental health. Participants were university students (N = 322) who completed the Perceived Stress Scale, the Satisfaction with Life Scale, and short forms of the trait scale of the Spielb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…By the time of data collection, the country still grappled with vaccine rollout challenges, public apprehension, and the socio-economic repercussions of the pandemic. Restrictions varied throughout this period as the government sought to balance public health needs with socio-economic realities (Padmanabhanunni et al, 2023a). The majority of participants were women (77%), and the mean age was 26.01 (SD = 10.19).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…By the time of data collection, the country still grappled with vaccine rollout challenges, public apprehension, and the socio-economic repercussions of the pandemic. Restrictions varied throughout this period as the government sought to balance public health needs with socio-economic realities (Padmanabhanunni et al, 2023a). The majority of participants were women (77%), and the mean age was 26.01 (SD = 10.19).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…3 Estrada-Araoz EG, et al positivos los ingresos, la satisfacción laboral, el cumplimiento de las necesidades, la resiliencia y las relaciones sociales y el apoyo. (35) Contrariamente, se ha comprobado que el desempleo, el estrés, la ansiedad y la depresión actúan como elementos que disminuyen la satisfacción con la vida. (36) Investigaciones previas han enfatizado que una mayor satisfacción con la vida no solo anticipa el bienestar mental futuro de un individuo, sino que también se correlaciona positivamente con un rendimiento académico destacado y un bienestar general en estudiantes de educación superior, al mismo tiempo que reduce los riesgos psicológicos para su salud.…”
Section: Satisfacción Con La Vidaunclassified
“…More recently, in a survey of 907 Polish participants, life satisfaction was negatively correlated with health-related worries about COVID-19 [46]. Some studies have shown that life satisfaction may have a mediating/moderating role in the relationship between depressive symptomatology and psychosocial well-being in the context of the pandemic [47,48]. Altogether, engaging in coping behaviours and higher life satisfaction appear to reduce or buffer against psychological distress, but there is a paucity in the literature regarding the role of these variables as moderators between sociodemographic/COVID-related variables and distress, particularly as far as they relate to Chinese Canadians.…”
Section: Coping and Life Satisfactionmentioning
confidence: 99%